2020
DOI: 10.1029/2019jg005577
|View full text |Cite
|
Sign up to set email alerts
|

Key Components and Contrasts in the Nitrogen Budget Across a U.S.‐Canadian Transboundary Watershed

Abstract: Watershed nitrogen (N) budgets provide insights into drivers and solutions for groundwater and surface water N contamination. We constructed a comprehensive N budget for the transboundary Nooksack River Watershed (British Columbia, Canada, and Washington, USA) using locally derived data, national statistics, and standard parameters. Feed imports for dairy (mainly in the United States) and poultry (mainly in Canada) accounted for 30% and 29% of the total N input to the watershed, respectively. Synthetic fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 93 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Perhaps a portion of manure produced by dairies is exported from the watershed or, in the case of N, losses from NH 3 volatilization could be larger than 20%. A recent N budget in the Nooksack River Basin found that 32% of total N losses were due to volatilization; three quarters of which were attributed to dairy manure alone (Lin et al., 2020). The growing dairy industry within the lower Yakima valley has led to major efforts to manage nutrients, such as the passage of the Dairy Nutrient Management Act, 1998 (Washington State) (RCW 90.64).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Perhaps a portion of manure produced by dairies is exported from the watershed or, in the case of N, losses from NH 3 volatilization could be larger than 20%. A recent N budget in the Nooksack River Basin found that 32% of total N losses were due to volatilization; three quarters of which were attributed to dairy manure alone (Lin et al., 2020). The growing dairy industry within the lower Yakima valley has led to major efforts to manage nutrients, such as the passage of the Dairy Nutrient Management Act, 1998 (Washington State) (RCW 90.64).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Lin et al. (2020), we assumed these volatilization losses happened during CAFO housing and the remainder was applied to fields. We did not account for manure exports from the basin but rather assumed all CAFO waste was either applied within watershed boundaries or lost via volatilization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations